Penggunaan Turunan Parsial untuk Analisis Risiko Keuangan dan Ekonomi - Tiara Febrianti Br Panjaitan; Valeri Agatha Br Sihombing; Vauline Christin Octavia Siregar (Jurnal Riset Ekonomi dan Akuntansi, 2025)
Partial derivatives play an important role in analyzing the dynamics of financial and economic systems involving many variables. This research explores the application of partial derivatives in financial risk models, including calculating portfolio sensitivity, volatility analysis, and estimating value at risk. Apart from that, it is also applied to economic models to analyze the impact of changes in economic variables on aggregate output. The case studies involve the use of partial derivatives in the Black-Scholes model for financial options and the IS-LM model in macroeconomics. The research results show that this mathematical approach increases prediction accuracy and helps strategic decision making.